Overexpression of tryptophan decarboxylase and strictosidine synthase enhanced terpenoid indole alkaloid pathway activity and antineoplastic vinblastine biosynthesis in Catharanthus roseus - Sharma, Abhishek; Verma, Priyanka; Mathur, Archana; Mathur, Ajay (Protoplasma, 2018)
Terpenoid indole alkaloid (TIA) biosynthetic pathway of Catharanthus roseus possesses the major attention in current metabolic engineering efforts being the sole source of highly expensive antineoplastic molecules vinblastine and vincristine. The entire TIA pathway is fairly known at biochemical and genetic levels except the pathway steps leading to biosynthesis of catharanthine and tabersonine. To increase the in-planta yield of these antineoplastic metabolites for the pharmaceutical and drug industry, extensive plant tissue culture-based studies were performed to provide alternative production systems. However, the strict spatiotemporal developmental regulation of TIA biosynthesis has restricted the utility of these cultures for large-scale production. Therefore, the present study was performed to enhance the metabolic flux of TIA pathway towards the biosynthesis of vinblastine by overexpressing two upstream TIA pathway genes, tryptophan decarboxylase (CrTDC) and strictosidine synthase (CrSTR), at whole plant levels in C. roseus. Whole plant transgenic of C. roseus was developed using Agrobacterium tumefaciens LBA1119 strain having CrTDC and CrSTR gene cassette. Developed transgenic lines demonstrated up to twofold enhanced total alkaloid production with maximum ninefold increase in vindoline and catharanthine, and fivefold increased vinblastine production. These lines recorded a maximum of 38-fold and 65-fold enhanced transcript levels of CrTDC and CrSTR genes, respectively.